Relationships between Biomass Composition and Liquid Products Formed via Pyrolysis - Lin, Fan; Waters, Christopher L.; Mallinson, Richard G.; Lobban, Lance L.; Bartley, Laura E. (Frontiers in Energy Research, 2015)
Thermal conversion of biomass is a rapid, low-cost way to produce a dense liquid product, known as bio-oil, that can be refined to transportation fuels. However, utilization of bio-oil is challenging due to its chemical complexity, acidity, and instability – all results of the intricate nature of biomass. A clear understanding of how biomass properties impact yield and composition of thermal products will provide guidance to optimize both biomass and conditions for thermal conversion. To aid elucidation of these associations, we first describe biomass polymers, including phenolics, polysaccharides, acetyl groups, and inorganic ions, and the chemical interactions among them. We then discuss evidence for three roles (i.e., models) for biomass components in the formation of liquid pyrolysis products: (1) as direct sources, (2) as catalysts, and (3) as indirect factors whereby chemical interactions among components and/or cell wall structural features impact thermal conversion products. We highlight associations that might be utilized to optimize biomass content prior to pyrolysis, though a more detailed characterization is required to understand indirect effects. In combination with high-throughput biomass characterization techniques, this knowledge will enable identification of biomass particularly suited for biofuel production and can also guide genetic engineering of bioenergy crops to improve biomass features.